Evaluasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) RSUD Gambiran Kediri menggunakan Framework Human, Organization, and Technology-Fit (HOT-FIT) Model - Evita Oktaviana; Widhy Hayuhardhika Nugraha Putra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Hospital Management Information System (SIMRS) is an information system which is used for process data into information used for the hospital services. SIMRS at Gambiran Kediri Hospital have problems related to technology such as frequent errors in system support devices, slow access networks, and some features were'nt functioning properly. Related to humans which is human errors. Related to the organization such as management support is still lacking and training is not evenly distributed. These things can cause a decrease in the quality of patient care in hospitals. The purpose of this research is to evaluate SIMRS in order to describe the problems of the current system condition using the HOT-Fit Model Framework and provide recommendations for SIMRS improvements to improve hospital services. Data was collected by distributing questionnaires to 135 users of SIMRS in hospitals were processed using descriptive statistical techniques and interviewing 11 informants which collected using triangulation techniques. The results showed that the technology aspect got a score of 73.52%, the human aspect got a score of 74.77%, the organization aspect got a score of 81.35%, the net benefits aspect got a score of 76.20%. Based on the problems obtained from this research, hospital need to improve and develop the information systems in order to meet hospital's needs in the future to provide maximum service.